Business Model Canvas for SIEGA Autobox Automated Locker - Stephani Inggrit Inggrit Swastini Dewi; Andre Kurniawan Pamudji; Agustina Alam Anggitasari (Soegijapranata Catholic University, 2024)
SIEGA Autobox is an innovative locker system designed to reduce physical interaction during transactions. It was developed in response to the COVID-19 pandemic. The system uses IoT and cashless payments to enable remote control and secure purchases. Initially, SIEGA Autobox was used to assist school canteen businesses that were struggling due to activity restrictions caused by COVID-19. Since COVID-19 has become endemic, the use of SIEGA Autobox lockers must be adapted to the needs of the times. This study aims to find the most effective business model for SIEGA Autobox using the Business Model Canvas (BMC) framework. The research suggests that the most suitable business model involves schools selling products directly through lockers. Based on interviews with Nusaputera National School and Theresiana 1 High School PICs, as well as the generated Business Model Canvas, the most suitable business model involves schools selling products directly through lockers. These products, sold by students, instructors, staff, or parents, typically have a medium to high economic value and a lengthy shelf life. To enhance locker awareness, schools could hold events such as open houses and publicize them on social media. Revenue would be generated through product sales or profit sharing with partner vendors and DBI (Dunia Bayar Indonesia).